# Question #1d80c

paranthesis first :)

#### Explanation:

$\left(7 - 5\right) \cdot 3 \implies$ first $\left(7 - 5\right) = 2$ then multiplication $2 \cdot 3 = 6$

$18 - 5 + 3$ from left to right $18 - 5 = 13 + 3 = 16$

$\left(19 + 4\right) - \frac{8}{2}$ first $\left(19 + 4\right)$ then $\left(\frac{8}{2}\right)$ and finally subtraction

$23 - \frac{8}{2} = 23 - 4 = 19$

Sep 20, 2016

$6 , 16 , 19$

#### Explanation:

Count the number of terms in each expression first.

IN each term, do brackets first,
then multiply and divide

$\text{ "color(red)((7-5)) xx 3" } \leftarrow$ all one term. Brackets first
=$\text{ } \textcolor{red}{2} \times 3$
=$\textcolor{w h i t e}{\times \times} 6$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

$18 - 5 + 3 \text{ } \leftarrow$ there are 3 terms

Work left to right

$= 13 + 3 = 16$

OR re-arrange the terms with the subtract at the end.

NOTE!! only 5 is being subtracted!! Do not add 5+3!

$18 + 3 - 5 = 16$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
$\textcolor{red}{\left(9 + 14\right)} \textcolor{b l u e}{- 8 \div 2} \text{ } \leftarrow$ there are 2 terms - get two answers

=$\textcolor{w h i t e}{\times x l} \textcolor{red}{23} \textcolor{b l u e}{- 4} \text{ }$ do 2 calculations, one in each term.

=$\text{ } 19$
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~